Дистрибуција на PIA полиморфизмот на тромбоцитниот гликопротеин GP IIIa во македонскта популација - Павковиќ, М; Стрезова, А; Петличковски, А; Арсов, Т; Спироски, М (Македонско лекарско друштво, 2004)
Human platelet antigen (HPA) system consist of more than twelve bi-allelic antigen polymorphisms due to a single base pare substitution that leads to an amino acid change in a expressed platelet glycoprotein. Polymorphism of a human platelet glycoprotein GP IIIa (HPA 1 or PlA) is one of the important factors in alloimunization that causes neonatal alloimmune thrombocytopenia and refractoriness to platelet transfusion. GP IIIa is a part of a platelet membrane receptor for fibrinogen and von Willebrand factor, and it has an important role in platelet aggregation. The purpose of this study was to type a random sample of Macedonian population for HPA-1 alleles, in order to obtain genetic population data. A total of 216 Macedonian volunteers were genotype for this polymorphism using the method of RFLP (restriction fragment length polymorphism). Distribution of PlA genotypes in Macedonian population was PlA 1/1=166, PlA1/2=46 and PlA2/2=4. The allele frequencies were 0.77 for HPA-1a (PlA 1) and 0.23 for HPA-1b (PlA 2). Our population displayed a slightly higher proportion of the HPA-1b allele (0.23), but not significantly different from other Caucasian population.
DISTRIBUTION OF PlA POLYMORHISM OF PLATELET GLYCOPROTEIN GP IIIa IN MACEDONIAN POPULATION